Spiritualités et prisons au xviie siècle - Sophie Houdard (Les Dossiers du GRIHL)
Based on Mrs. Guyon’s experience in prison during the trial of “quiétisme”, we would like to clarify the relationship between imprisonment, as a social situation and a lived experience, and the prison as described in the writings that recount and define the mystical experience. We believe that this rarely observed role of imprisonment in writing, as a place for writing and an expression of the experience, is crucial.